Enhancing stability of CsPbBr3 nanocrystals light‐emitting diodes through polymethylmethacrylate physical adsorption. Issue 3 (16th August 2020) - Wang, Zhaojin; Xiao, Xiangtian; Shen, Jian; Liu, Pai; Wu, Dan; Tang, Xiaobing; Mei, Guanding; Sun, Jiayun; Yang, Hongcheng; Li, Xiang; Wu, Zhenghui; Xie, Qifei; et al.
Abstract: Boosting the efficiency and lifetime of all inorganic metal halide perovskite nanocrystals (PeNCs) based light‐emitting diodes (PeLEDs) will promote the application of PeNCs in displays and lighting. However, achieving high‐stability CsPbBr3 NCs is still a critical challenge. In this study, a physical adsorption of polymethylmethacrylate (PMMA) on the surface of CsPbBr3 NCs is proven effective to enhance CsPbBr3 NCs stability by reducing the surface energy and preventing the attack of water and oxygen molecules. It also alleviates the energy transfer between neighboring NCs and greatly reduces the thin film roughness by suppressing the agglomeration of the CsPbBr3 NCs within films. Specifically, compared with CsPbBr3 NCs without PMMA adsorption, the photostability under the illumination of continuous ultraviolet light (96 hours) and storage stability under 0 °C (60 days) of the proposed CsPbBr3 NCs with PMMA adsorption are therefore improved by >10 times and four times, respectively. Moreover, since the energy transfer between CsPbBr3 NCs and the agglomeration of CsPbBr3 NCs within films have been suppressed dramatically by the physical absorbed PMMA, the maximum luminance of as‐fabricated LED devices is promoted from 5000 to 13, 800 cd m −2 with alleviated roll‐off effect. The operational lifetime of the LED devices is also improved by 5.7 times owing to PMMA preventing the attack of water and oxygen molecules. Abstract : A physical adsorption of polymethyl methacrylate (PMMA) on the surface of CsPbBr3 nanocrystals (NCs) is proven effective to enhance CsPbBr3 NCs stability by reducing the surface energy and preventing the attack of water and oxygen molecules. Moreover, the maximum luminance of as‐fabricated LED devices is also promoted significantly by suppressing the agglomeration of the CsPbBr3 NCs within films and reducing the hole injection barrier.